Time-dependent catalytic activity in aging condensates - Wei Kang; Zhiyue Wu; Xinzhi Huang; Hongbin Qi; Jiaxuan Wu; Jiahui Wang; Jing Li; Sijin Wu; Byung-Ho Kang; Bo Li; Juncai Ma; Chuang Xue (Nature Communications)
Abstract Biomolecular condensates are dynamic cellular compartments that concentrate proteins and enzymes to regulate biochemical reactions in time and space. While these condensates can enhance enzyme activity, how this function changes as condensates age remains poorly understood. Here, we design synthetic catalytic condensates that selectively recruit enzymes to investigate this temporal evolution. We show that catalytic condensates exhibit time-dependent activity: they initially accelerate enzymatic reactions but gradually lose efficiency due to the transition from liquid-like to solid-like states. This aging process, characterized by protein aggregation and loss of selective barriers, impairs enzyme function both in vitro and living cells. We further demonstrate that small molecules which influence aging dynamics can modulate catalytic efficiency of condensates. Our findings show that condensate aging as a key regulator of enzymatic activity and provide crucial insights for designing functional synthetic condensates.